Integrative Comparative Biology of Two Snakehead Fish (Channa spp.): Biosystematic, Anatomical, and Hematophysiological Evidence from South Kalimantan, Indonesia - Rakmawati Rakmawati; Anni Nurliani; Abdul Gafur; Hameda Dhaka Kusuma Taufiq; Najwah Najwah; Suhendra Suhendra (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract   Highlight Research 1. Morphological profile and morphological variation of Channa striata and Channa micropeltes. 2. Morphometric and Meristic study of Channa striata and Channa micropeltes. 3. Anatomical profile of Channa striata and Channa micropeltes. 4. Physiological profile of Channa striata and Channa micropeltes.   Abstract Kalimantan has two typical types of snakehead fish, namely the Haruan fish (Channa striata) and the Toman fish (Channa micropeltes). This study aims to examine the morphological, anatomical, and physiological profiles of two types of snakehead fish commonly found in Kalimantan. A total of 50 fish samples of each were obtained from local markets in Banjarbaru, South Kalimantan. The methods used included sampling and selection, handling, observation, and dissection of C. striata and C. micropeltes, which included observations of biosystematic, anatomical, and physiological profiles. Biosystematic parameters include observations of morphological variations, morphometric, and meristic profiles, and analysis was carried out using the PCA, calculating the length-weight relationship, and condition factors. For anatomical parameters, dissection was carried out to observe and identify the organs. Organ profiles were analyzed for the relationship between organ weight and total fish weight. T-test was also performed to analyze any significant differences between the two fish species. For physiological parameters, blood was taken to analyze the profile thoroughly, and analyzed using the microhematocrit, Sahli, and Giemsa methods. The results of the biosystematic analysis highlight morphological variation and the relationship between total body length and body weight. There are uniform data range between C. striata and C. micropeltes with the eigenvalue ranges of 84-86%, and the growth pattern is negative allometry. Anatomical parameters revealed a tri-branched gut structure. For the t-test, there is a significant relationship between total organ weight and total body weight in the fish, with the R value was greater than R table value. The hematological profiles differed between species. Detailed research is needed on the biological profiles of C. striata and C. micropeltes, particularly regarding differences in their profiles based on sex, complete physiological data, and in-depth, comprehensive ecological profile data.